Comprehensive Approaches of Nanoparticles for Growth Performance and Health Benefits in Poultry: An Update on the Current Scenario. (17th September 2022) - Ahmad, Ilyas; Mashwani, Zia-Ur-Rehman; Raja, Naveed Iqbal; Kazmi, Abeer; Wahab, Abdul; Ali, Amir; Younas, Zohaib; Yaqoob, Saman; Rahimi, Mehdi
Abstract : Currently, providing nutritious food to all people is one of the greatest challenges due to rapid human population growth. The global poultry industry is a part of the agrifood sector playing an essential role in food insecurity by providing nutritious meat and egg sources. However, limited meat production with less nutritional value is not fulfilling the higher market demands worldwide. Researchers are focusing on nanobiotechnology by employing phytosynthesized mineral nanomaterials to improve the growth performance and nutritional status of broilers as these mineral nanoparticles are usually absorbed in greater amounts from the gastrointestinal tract and exert enhanced biological effects in the target tissues of animals with greater tissue accumulation. These mineral nanoparticles are efficiently absorbed through the gastrointestinal tract and reach essential organs via blood. As a result, it enhances growth performance and nutritional value with less toxicity and tremendous bioavailability properties. In this review, the research work conducted in the recent past, on the different aspects of nanotechnology including supplementation of mineral nanoparticle in diet and their potential role in the poultry industry, has been concisely discussed.